Study of Effective Distribution Networks and Availability of Products at Hyperstar (Global Journal of Management and Business Research, 2013)
Hyperstar is most economical store with best quality produsts in different verity. It has 47 stores in 16 countries. Hyperstar management follows the roles of distribution networks. The availability of products at this store is very impressive. They have 100,000 products in their stock. They follow the Push and Pull strategies to supply chain management. Implementation of cyclic view of supply chain management is so much effective in hyperstore. In this research I collect data from the employees of hyperstar. The sample size is 10. SPSS software use to analyze the data. Chisquare test use to analyze the data also the T-test as well. Supply chain management and distribution networks can make much difference in the sales. Availability of products at hyperstar, only possible when they maintain their distribution networks.
Keywords: distribution networks; chain management; maintain their distribution networks